MAN SENTENCED TO LIFE TERM: SUN-SENTINEL Edition - Staff reports (Sun-sentinel (Fort Lauderdale, Fla.), 1987)
The Paz family died from multiple gunshot wounds from a rifle the younger Paz had recently purchased after a failed effort to buy a handgun from a Miami dealer, Metro-Dade homicide Sgt. Michael Diaz said in December.